Community based clinical program: the Medunsa physiotherapy students` experience - N. P. Taukobong (AOSIS, 2004)
Backgound: The aim of community based clinical training is t produce graduates who are responsive to the health needs of their communit It is envisaged that upon completion of training graduates would go back an serve their respective communities following exposure to community need Program evaluation should therefore allow students to express the inadequacie and strengths of the program. Aim: To evaluate the community-based clinical program through student's experiences. Methodology: A qualitative research design was used. End of block students reports for both third (8) and fourth (15) year physiotherapy students (n = 23) were used to collect the data. Responses in the reports were grouped into the following categories for purpose of data analysis: feeling about the block, suggestion/s and supervision. Results: The students described the community based clinical program as an unique learning experience which equipped them with the understanding of life within communities. Sixty five percent (65%) expressed satisfaction with the supervision given. The main complaints were amounts of paper work involved and clinical workload. Conclusion: The student's experiences indicated that the community-based clinical program within the MEDUNSA physiotherapy department realizes the goal of community-based clinical training as determined by WHO, except for inclusion of some multi-professional approaches and adaptation of the supervision provided.